Insights on Structure and Function of a Late Embryogenesis Abundant Protein from Amaranthus cruentus: An Intrinsically Disordered Protein Involved in Protection against Desiccation, Oxidant Conditions, and Osmotic Stress - Saucedo, Alma L.; Hernández-Domínguez, Eric E.; de Luna-Valdez, Luis A.; Guevara-García, Angel A.; Escobedo-Moratilla, Abraham; Bojorquéz-Velázquez, Esaú; del Río-Portilla, Federico; Fernández-Velasco, Daniel A.; Barba de la Rosa, Ana P. (Frontiers in Plant Science, 2017)
Late embryogenesis abundant (LEA) proteins are part of a large protein family that protect other proteins from aggregation due to desiccation or osmotic stresses. Recently, the Amarantus cruentus seed proteome was characterized by 2D-PAGE and one highly accumulated protein spot was identified as a Late Embryogenesis Abundant protein and was named AcLEA. In this work, AcLEA cDNA was cloned into an expression vector and the recombinant protein was purified and characterized. AcLEA encodes a 172 amino acid polypeptide with a predicted molecular mass of 18.34 kDa and estimated pI of 8.58. Phylogenetic analysis revealed that AcLEA is evolutionarily close to the LEA3 group. Structural characteristics were revealed by nuclear magnetic resonance (NMR) and circular dichroism (CD) methods. We have shown that recombinant AcLEA is an intrinsically disordered protein (IDP) in solution even at high salinity and osmotic pressures, but it has a strong tendency to take a secondary structure, mainly folded as α-helix, when an inductive additive is present. Recombinant AcLEA function was evaluated using E. coli as in vivo model showing the important protection role against desiccation, oxidant conditions and osmotic stress. AcLEA recombinant protein was localized in cytoplasm of Nicotiana benthamiana protoplasts and orthologs were detected in seeds of wild and domesticated amaranth species. Interestingly AcLEA was detected in leaves, stems, and roots but only in plants subjected to salt stress. This fact could indicate the important role of AcLEA protection during plant stress in all amaranth species studied.